Assessment of Buildings After Gorkha Earthquake 2015: A Case Study of Central Buildings of Kathmandu University, Nepal - Pradhan, P.M.; Adhikari, R.; Bhat, D.R. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
The major earthquake in April 25, 2015 of Mw 7.8 and aftershock of intensity Mw 7.3 on May 12, 2015 caused damages to the buildings of Kathmandu University, located at Dhulikhel, Nepal. The immediate assessment of those buildings was required in order to assure whether the buildings were safe for continuing academic and administrative activities. Rapid visual assessment was performed for each building and on that basis, preliminary recommendations for repairs were suggested. Buildings where heavy damages incurred, detailed investigation were sought, until then the restriction of occupancy in that building was recommended. Those buildings which experienced minor damages, were recommended for minor repair and retrofitting works.